2016
DOI: 10.1007/s11695-016-2104-5
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Knowledge as Determinants of Recommendation and Referral Behavior of General Practitioners and Internists

Abstract: This study showed that stigma plays a role when it comes to defining treatment pathways for patients with obesity. The question remains how this might influence the patients and their decision regarding their treatment selection. Interventions are required to make treatment decisions by physicians or patients independent of social pressure due to stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
3
26
0
4
Order By: Relevance
“…Attitudes and perceived experience were the most influencing factors on GPs referral intent, which is supported by our results. Knowledge and stigmatizing attitudes towards treatment options also seems to have an influence on referral behavior, as shown by a German study on weight loss surgery [16]. In addition, the availability of resources, such as the possibility for direct contact between GPs and referral providers and the location of the referral service, influences GP decisions [6,22,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes and perceived experience were the most influencing factors on GPs referral intent, which is supported by our results. Knowledge and stigmatizing attitudes towards treatment options also seems to have an influence on referral behavior, as shown by a German study on weight loss surgery [16]. In addition, the availability of resources, such as the possibility for direct contact between GPs and referral providers and the location of the referral service, influences GP decisions [6,22,29].…”
Section: Discussionmentioning
confidence: 99%
“…There are difficulties in making inferences from one country to another, in part, because of sociocultural and structural differences in health care systems. There have been some studies in Germany about stigmatizing attitudes in the general population [ 11 , 12 ] and health care providers [ 13 ], as well as surveys about treatment of obesity [ 14 16 ]. However, studies examining the link between attitudes and treatment practice in primary health care are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Global stigmatization of obesity increased over the past decades, also in healthcare providers [8]. It is a growing concern given the increasing prevalence of obesity [4,[9][10][11][12]. The society often considers obesity a "lifestyle-disease" and individuals with obesity are regarded to be responsible ("their own fault", "are inactive", "don't have self-control") [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Corrigan et al, concluded that the perceived stigma of mental illness is a major barrier to the seeking of psychosocial treatment . In addition, such studies on cancer patients have not been conducted, but there was one study that showed that physicians' stigma affects defining treatment pathways for patients with obesity . However, no study has been undertaken to investigate the effect of physicians' perceived stigma toward depression on referral for such treatment.…”
Section: Introductionmentioning
confidence: 99%